Saberes docentes na/da formação continuada de professores que ensinam matemática no ciclo de alfabetização - SILVA, Fabio Colins da (Universidade Federal do Pará, 2017)
In this dissertation, entitled “Teachers knowledge in continuing teacher training to teach Mathematics in cycle of the Literacy, aimed to investigate under what conditions the teaching knowledge are mobilized from the continuous training of literacy teachers. In this research the discussion was woven around the teaching knowledge mobilized in literacy practice. The themes make up this study: Knowledge Teachers; Continuing Teacher and Training and Literacy Mathematics, were discussed in the theoretical perspective of the Shulman (1986; 2005), Gauthier (2013) and Tardif (2014). For these authors the teachers are subjects that mobilized knowledge in classroom practice. Based in Imbernón (2009; 2011) built the discussion of the teaching training in a perspective of professional development. With regard to numeracy used studies of Fonseca (2004; 2009; 2014). For the author, the teaching of Mathematics can be done from the reading and writing of various genres, in other words, a mathematical literacy in perspective of the literacy. The research was context the federal program National Pact for Literacy in the Middle One. The locus of the investigation was the city of Marabá, Pará State, Brazil. The subjects of this study were five literacy teachers. The survey was conducted between March 2014 and January 2015. The construction of the information was given from the records of the activities carried out by literacy teachers during the municipal formation meetings, yours practice reports and their experience reports. The methodology used was the Textual Analysis Discourse. The analysis categories emerged from survey: a) the relationship with the mathematical knowledge; b) the teaching knowledge mobilized in practice literacy; and c) a new relationship with the mathematical knowledge. It can be argued that from the continuing education and everyday educational activities teachers mobilize a plurality of knowledge: Experience knowledge, content knowledge, pedagogical knowledge, curriculum knowledge and knowledge of the science of education, necessary for the practice literacy mathematics.